Ultrashort gain-switched pulse trains from laser diodes characterized by a single-shot up-conversion time microscope - Ryo Tamaki; Masataka Kobayashi; Aoi Maeshiro; Hidekazu Nakamae; Changsu Kim; Takashi Ito; Shaoqiang Chen; Jun Takeda; Hidefumi Akiyama; Ikufumi Katayama (Applied Physics Express)
Ultrashort pulse profiles from a gain-switched laser diode (GS-LD) were investigated using an up-conversion time microscope, which enables single-shot detection of ultrashort pulses from the GS-LD in the time domain. Sum-frequency generation between the positively chirped readout pulses and the negatively chirped GS-LD output pulses revealed partially-mode-locked characteristics of the GS pulses. The pulse trains, with a temporal width below 0.9 ps and a periodic interval of 5.3 ps, were confirmed to be consistent with their interferometric autocorrelation trace. The demonstrated single-shot measurements of ultrashort pulse profiles elucidate pulse-to-pulse characteristics in the time domain with sub-picosecond time resolution.